Seroprevalence of Brucellosis in Buffaloes of Malwa Region of Madhya Pradesh - Verma, Sachin; Jatav, G. P.; Shukla, Supriya; Jayraw, A. K.; Chauhan, H. C.; Shrivastava, Nidhi (International Journal of Livestock Research, 2019)
Brucellosis is one of the five main notifiable bacterial diseases of zoonotic importance in the world. The most widely used serological tests for diagnosis of brucellosis in animals are Rose Bengal plate test, standard tube agglutination test and enzyme linked immunosorbent assay. The present study was undertaken to assess the seroprevalence of brucellosis in 150 buffaloes belonging to different regions of Malwa tract and nearby areas of Indore district by using Rose Bengal plate test (RBPT), indirect enzyme linked immunosorbent assay (i-ELISA), Milk ring test (MRT) and California mastitis test (CMT) for detecting anti-Brucellaantibodies. Sero-prevalence of brucellosis in buffaloes by using RBPT, i-ELISA, MRT and CMT was recorded as 13.33% (20/150), 00% (00/150), 38.88% (7/18) and 55.55% (10/18), respectively.